2016
DOI: 10.1590/1678-4685-gmb-2014-0387
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of MAGO and Y14 genes in Hevea brasiliensis

Abstract: Mago nashi (MAGO) and Y14 proteins are highly conserved among eukaryotes. In this study, we identified two MAGO (designated as HbMAGO1 andHbMAGO2) and two Y14 (designated as HbY14aand HbY14b) genes in the rubber tree (Hevea brasiliensis) genome annotation. Multiple amino acid sequence alignments predicted that HbMAGO and HbY14 proteins are structurally similar to homologous proteins from other species. Tissue-specific expression profiles showed that HbMAGO and HbY14 genes were expressed in at least one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…As mentioned above, the nucleolus and particularly CBs play important roles in snRNP synthesis, which are essential for the formation of spliceosomes (reviewed in Love et al, 2017 ). The EJC and particularly two of its core subunits such as MAGO and Y14, are widely known to have essential multiple developmental roles in animals, whereas information for such roles in plants is more limited (Gong and He, 2014 ; Yang et al, 2016 ). It has been shown that MAGO proteins are responsible for male fertility ( Physalis floridana ; He et al, 2007 ), pollen grain development (Arabidopsis; Park et al, 2009 ) and spermatogenesis ( Marsilea vestita ; Boothby and Wolniak, 2011 ).…”
Section: Plant Growth and Developmentmentioning
confidence: 99%
“…As mentioned above, the nucleolus and particularly CBs play important roles in snRNP synthesis, which are essential for the formation of spliceosomes (reviewed in Love et al, 2017 ). The EJC and particularly two of its core subunits such as MAGO and Y14, are widely known to have essential multiple developmental roles in animals, whereas information for such roles in plants is more limited (Gong and He, 2014 ; Yang et al, 2016 ). It has been shown that MAGO proteins are responsible for male fertility ( Physalis floridana ; He et al, 2007 ), pollen grain development (Arabidopsis; Park et al, 2009 ) and spermatogenesis ( Marsilea vestita ; Boothby and Wolniak, 2011 ).…”
Section: Plant Growth and Developmentmentioning
confidence: 99%
“…In rice, both OsMAGO2 and OsY14b genes show high sensitivity to a variety of abiotic stresses (Gong and He 2014). In Hevea brasiliensis, HbMAGO and HbY14 genes have different expression patterns in response to ethylene and jasmonate treatments (Yang et al 2016). AteIF4AIII shares functions in abiotic stress adaptation in Arabidopsis .…”
Section: Discussionmentioning
confidence: 99%
“…MAGO, Y14 and eIF4AIII genes are involved in the growth, development and reproduction processes in some plant species (Park et al 2009; Boothby and Wolniak 2011; Gong and He 2014; Gong et al 2014a; Ihsan et al 2015; Huang et al 2016). MAGO and Y14 are regulated by ethylene and jasmonate and MAGO may be involved in the aggregation of rubber particles in Hevea brasiliensis (Yang et al 2016). Arabidopsis eIF4AIII is co-localized with AtMAGO and AtY14 proteins, and its subcellular localization mode is altered in response to hypoxia or by different phosphorylation states (Koroleva et al 2009; Cui et al 2016).…”
Section: Introductionmentioning
confidence: 99%